1975
DOI: 10.1083/jcb.64.3.528
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of chromatin substructure: upsilon bodies.

Abstract: Spread chromatin fibers, from isolated eucaryotic nuclei, reveal linear arrays of spherical particles (o bodies), about 70 A in diameter, connected by thin filaments about 15 A wide. These particles have been observed in freshly isolated nuclei from rat thymus, rat liver, and chicken erythrocytes. In addition, v bodies can be visualized in preparations of isolated sheared chromatin, and in chromatin reconstructed from dissociating solvent conditions (i.e., high urea-NaCl concentration). As a criterion for pert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(43 citation statements)
references
References 36 publications
(42 reference statements)
3
40
0
Order By: Relevance
“…3, arrows). The granules are the same sizes as the v-bodies re reported by Olins and Olins (1974), Woodcock et al (1976) and Howze et al (1976), but the tiny filaments connecting v-bodies as reported by Olins and Olins (1974) and Howze et al (1976) could not be observed.…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…3, arrows). The granules are the same sizes as the v-bodies re reported by Olins and Olins (1974), Woodcock et al (1976) and Howze et al (1976), but the tiny filaments connecting v-bodies as reported by Olins and Olins (1974) and Howze et al (1976) could not be observed.…”
Section: Methodssupporting
confidence: 65%
“…2). Olins and Olins (1974) and Wood cock et al (1976) concluded that the extended chromatin threads have a "beads on-a-string" substructure, with particles called "v-bodies" which are about 70 A in diameter and are connected by DNA fibers of about 15 A diameter . Howze et al (1976) observed fine fibrils of about 89+11 A length between particles in the chromosomes of Chinese hamsters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…110A (4)(5)(6). Nucleosomes are comprised of about 200 base pairs of DNA wound around a complex containing two each of the four major histones (11)(12)(13)(14)(15)(16)(17). Transcriptionally active and inactive regions of cellular chromatin are both organized in this basic manner (18)(19)(20), although there is some structural difference between them, as evidenced by a selective deoxyribonuclease I sensitivity of active genes (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…One basic structural component of the chromosome results from the organization of histone and DNA into a regular array of nucleosomes (1)(2)(3)(4)(5)(6)(7). This basic unit of structure involves about 190 base pairs of DNA complexed with two each of the four major histones and encompasses virtually all genomic sequences.…”
mentioning
confidence: 99%